2020
DOI: 10.3390/ijms21041355
|View full text |Cite
|
Sign up to set email alerts
|

Artocarpus lakoocha Extract Inhibits LPS-Induced Inflammatory Response in RAW 264.7 Macrophage Cells

Abstract: Artocarpus lakoocha Roxb. (AL) has been known for its high content of stilbenoids, especially oxyresveratrol. AL has been used in Thai traditional medicine for centuries. However, the role of AL in regulating inflammation has not been elucidated. Here we investigated the molecular mechanisms underlying the anti-inflammation of AL ethanolic extract in RAW 264.7 murine macrophage cell line. The HPLC results revealed that this plant was rich in oxyresveratrol, and AL ethanolic extract exhibited anti-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Natural polyphenolic phytochemicals have emerged as possible anti-neuroinflammatory agents. In particular, our previous study demonstrated that the Artocarpus lakoocha Roxb, containing a high amount of oxyresveratrol (OXY), could suppress lipopolysaccharide (LPS)-induced inflammatory response via inhibiting PI3K/AKT, MAPK, and NF-κB cascades in murine macrophages [ 10 ]. In our current study, we focused mainly on investigating anti-neuroinflammatory effects of OXY, reported to pass the blood–brain barrier (BBB) and exert neuroprotective effects in rodents [ 12 , 15 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural polyphenolic phytochemicals have emerged as possible anti-neuroinflammatory agents. In particular, our previous study demonstrated that the Artocarpus lakoocha Roxb, containing a high amount of oxyresveratrol (OXY), could suppress lipopolysaccharide (LPS)-induced inflammatory response via inhibiting PI3K/AKT, MAPK, and NF-κB cascades in murine macrophages [ 10 ]. In our current study, we focused mainly on investigating anti-neuroinflammatory effects of OXY, reported to pass the blood–brain barrier (BBB) and exert neuroprotective effects in rodents [ 12 , 15 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxyresveratrol ( trans -2,3′,4,5′-tetrahydroxystilbene, OXY) is a polyphenolic molecule, and it can be extracted from different plants, including Artocarpus lakoocha ( A. lakoocha ) [ 10 , 11 ]. Furthermore, OXY exerts several pharmacological activities, especially anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…(Moraceae), which has been used in Thai traditional medicine as an antioxidant and to treat inflammatory and parasitic diseases [ 30 , 31 , 32 ]. Recently, many studies have been performed to investigate the pharmacological effects of oxyresveratrol: in particular, it has been reported to suppress lipopolysaccharide-induced inflammatory response in murine models [ 31 , 33 , 34 ] and to exert its anti-inflammatory effects mainly by downregulating the release of various cytokines [ 12 , 13 , 14 , 15 ]. As far as we know, no investigations have been made on the effect of oxyresveratrol on the functional activity of human DCs, which play an essential role in activation of inflammation and immune reaction [ 1 , 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic effect is associated with the abundance of phenolics, such as flavonoids, stilbenoids, dihydrochalcones, dihydrobenzoxanthones and prenylated flavonoids [12]. Single metabolites reported in vivo antimalarial [13], inhibition of LPS-induced inflammation [14], α-glucosidase inhibitory [15], TRAILresistance overcoming with antiviral [16], and anticancer [17] activities. Alkylated flavonoid Artonin E from A. elasticus also revealed considerable cytotoxic effect in MCF-7 human breast cancer cells by ROS mediated mitochondrial pathway [18,19].…”
Section: Introductionmentioning
confidence: 99%